Pegylated gold nanoparticles interact with lipid bilayer and human serum albumin and transferrin - Elżbieta Okła; Sylwia Michlewska; Adam Buczkowski; Serafin Zawadzki; Katarzyna Miłowska; Javier Sánchez-Nieves; Rafael Gómez; Francisco Javier de la Mata; Maria Bryszewska; Janusz Blasiak; Maksim Ionov (Scientific Reports)
Abstract Gold nanoparticles (AuNPs) are potentially applicable in drug/nucleic acid delivery systems. Low toxicity, high stability, and bioavailability are crucial for the therapeutic use of AuNPs and they are mainly determined by their interactions with proteins and lipids on their route to the target cells. In this work, we investigated the interaction of two pegylated gold nanoparticles, AuNP14a and AuNP14b, with human serum proteins albumin (HSA) and transferrin (Tf) as well as dimyristoyl-phosphatidylcholine (DMPC) liposomes, which can be a representative of biomembranes. We showed that AuNP14a/b interacted with HSA and Tf changing their electrical, thermodynamic, and structural properties as evidenced by dynamic light scattering, zeta potential, transmission electron microscopy, circular dichroism, fluorescence quenching, and isothermal titration calorimetry. These nanoparticles penetrated the DMPC membrane suggesting their ability to reach a target inside the cell. In most of the effects, AuNP14b was more effective than AuNP14a, which might result from its more positive charge. Further studies are needed to evaluate whether the interaction of AuNP14a/b with HSA and Tf is safe for the cell/organism and whether they may safely penetrate natural membranes.